2022
DOI: 10.1038/s41467-022-34526-9
|View full text |Cite
|
Sign up to set email alerts
|

T cell responses at diagnosis of amyotrophic lateral sclerosis predict disease progression

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease, involving neuroinflammation and T cell infiltration in the central nervous system. However, the contribution of T cell responses to the pathology of the disease is not fully understood. Here we show, by flow cytometric analysis of blood and cerebrospinal fluid (CSF) samples of a cohort of 89 newly diagnosed ALS patients in Stockholm, Sweden, that T cell phenotypes at the time of diagnosis are good predictors of disease outcome. High freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…Importantly, CSF of ALS patients exhibits an expansion of a T cell subpopulation expressing eomesodermin, which drives IFN-𝝲 expression. 32 IFN-𝝲 is permeable to the blood spinal barrier, particularly in the cervical region, implying that T cells impacted by peripheral inflammation might expose motor neurons to IFN-𝝲. [33][34][35] Moreover, Bonney et al showed that IFN-𝝲 even promotes its permeability to the blood-brain barrier, implying that uncontrolled IFN-𝝲 secretion may broadly affect the physiology of the entire CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CSF of ALS patients exhibits an expansion of a T cell subpopulation expressing eomesodermin, which drives IFN-𝝲 expression. 32 IFN-𝝲 is permeable to the blood spinal barrier, particularly in the cervical region, implying that T cells impacted by peripheral inflammation might expose motor neurons to IFN-𝝲. [33][34][35] Moreover, Bonney et al showed that IFN-𝝲 even promotes its permeability to the blood-brain barrier, implying that uncontrolled IFN-𝝲 secretion may broadly affect the physiology of the entire CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that T-cell infiltration and clonal expansion is enhanced in neurodegenerative disorders such as AD, [126][127][128][129][130] PD, [131][132][133][134][135] ALS, 136,137 and MS. [138][139][140][141] Although some of these disorders have T-cell antigens that are more clearly defined such as in MS and PD, there is still a significant need for further investigating the antigenic source/breadth and the mechanisms in which they induce T-cell activation.…”
Section: Pathog Eni C-derived Anti G En S In N E U R O D E G E N E R ...mentioning
confidence: 99%
“…They found that monocytes signal to clonal CD8 + T cells via CXCL16-CXCR6 in patients with cognitive impairment. Yazdani et al [ 82 ] have used the same technique to examine the CSF of patients with amyotrophic lateral sclerosis (ALS) and described clonally expanded CD4 + and CD8 + T cells with characteristic patterns of gene expression.…”
Section: Elements Of the Blood-csf Barrier And The Csf And Glymphatic...mentioning
confidence: 99%
“…In ALS, Yazdani et al [ 82 ] have found that T cell phenotypes in blood and CSF are good predictors of disease progression with high CD4 + FOXP3 − effector T cell expression being associated with poor survival, whereas a high frequency of Treg cells was associated with better survival. They also found evidence of clonally expanded CD4 + and CD8 + cells in CSF and propose that modulating adaptive immunity is a therapeutic option for ALS.…”
Section: Neurological Disordersmentioning
confidence: 99%